Fatty acid composition and tocopherol content in four Tunisian Hypericum species: Hypericum perforatum, Hypericum tomentosum, Hypericum perfoliatum and Hypericum ericoides Ssp. Roberti - Karim Hosni; Kamel Msaâda; Mouna Ben Taârit; Brahim Marzouk (Arabian Journal of Chemistry, 2017)
The fatty acid and tocopherol constituents of four Tunisian Hypericum species: Hypericum perforatum, Hypericum perfoliatum, Hypericum tomentosum and the endemic subspecies Hypericum ericoides Ssp. Roberti were analyzed in detail. Results revealed that all species have very low total lipid contents (0.6–3.5 mg/g dw). The major identified fatty acids were linoleic (11.21–37.62%), oleic (11.2–23.27%) and palmitic acid (4.03–20.67%). Analysis of tocopherols allowed the identification of three isoforms (α-, γ- and δ-tocopherols). The δ-tocopherol (2.69–22.32 μg/g dw) was found as the prominent tocopherol. Quantitative differences in the fatty acid and tocopherol profiles between Hypericum species were observed. H. perfoliatum and H. ericoides Ssp. Roberti showed significantly higher content of linoleic acid, whereas significantly higher amounts of oleic acid and palmitic acid were detected in H. perforatum and H. tomentosum, respectively. Multivariate analysis (principal components analysis and hierarchical cluster analysis) based on the fatty acid profiles joined H. perfoliatum and H. ericoides in one group, while H. perforatum and H. tomentosum were joined in a second group at the same linkage distance. With the exception of H. perforatum, this is the first report on the fatty acid and tocopherol constituents of H. perfoliatum, H. tomentosum and H. ericoides Ssp. Roberti.